Disclosure to unknowing victims in criminal justice investigations: Questions of vulnerability, ethics and practice - Ost, Suzanne (International journal of police science & management, 2024)
This article explores the situation in which a victim who has been identified during a criminal justice investigation is unaware of the crime committed against them. We argue that unknowing victims possess a unique vulnerability because discovering their victim status is highly likely to have harmful effects. Where law enforcement officers (LEOs) remain unaware of the victim's knowledge of the crime, this should be perceived as a clue to potential vulnerability. Any subsequent disclosure of the crime to an unknowing victim is an external intervention that exposes them to the risk of harm, thereby raising significant ethical questions. Yet the ethical ramifications of disclosure are not considered in the policing literature and there is no specific professional guidance in England and Wales (and beyond) on this situation. Focusing on two of the primary crime contexts in which a victim can be unknowing (sexual offences and fraud), we scrutinise the ethical issues surrounding LEOs disclosing to an unknowing victim, aligning our analysis with the College of Policing's Code of Ethics and vulnerability-related risks guidelines, and a therapeutic jurisprudence approach to policing.